Exploring Adolescents’ Future Time Orientation: The Italian Validation of the Scale and Links to Sustainability - Sara Santilli; Maria Cristina Ginevra; Vinicius Coscioni (Behavioral Sciences)
Adolescents today face significant exposure to social inequalities and environmental crises, including the impacts of climate change, such as heatwaves, floods, and droughts. In addition, they encounter various forms of inequality, such as job insecurity, lack of affordable housing, and growing mental health challenges. Future perception is an essential variable in understanding how adolescents address these social and environmental challenges. Thus, this study adapted the Future Time Orientation Scale (FTOS) to the Italian context, assessing its validity and reliability for measuring psychological future orientation among Italian-speaking adolescents. Two studies were conducted: the first validated the FTOS through exploratory and confirmatory factor analyses, revealing two factors, “Impact” and “Distance”. The second study examined the relationship between future time orientation, future orientation in the professional field, and adolescents’ propensity to consider global challenges related to sustainable development. The results indicated that future orientation fully mediates the relationship between future time orientation and the tendency to consider global challenges in career decision-making. These findings underscore the importance of future orientation in shaping adolescents’ sustainable career choices and suggest that career interventions promoting future time orientation may enhance their engagement with global challenges.